Maritime history: A health check. (May 2017) - Ojala, Jari; Tenold, Stig
This article discusses publishing trends within maritime history. The first part uses a purpose-built database to analyse information on more than 300 authors who have published in the International Journal of Maritime History, the leading journal within the field. The analysis of these data reveals that there is a substantial heterogeneity among those that publish maritime history articles. The second part of the article compares the development of publishing within maritime history with two other sub-disciplines, 'world history' and 'global history'. Finally, the authors argue that maritime history is a very good entry point for other types of research, both historical analyses and other types of scholarship.